TRANSLATION STRATEGIES OF CULTURE-SPECIFIC TERMS IN THE TOURISM TEXTS SEPOTONG UBUD DI YOGJAKARTA AND MENGANTARKAN PULANG SANG PELINGSIR - Zainal Arifin (p-ISSN 2356-0576, 2014)
Abstract: The study aims to analyze and describe the translation strategies of culture-specific-words in the tourism texts Mengirim Pulang Sang Pelingsir and Sepotong Ubud di Yogyakarta. It used a descriptive-qualitative. The data were the specific-culture words, terms, or expressions in the tourism texts Sepotong Ubud di Yogyakarta and its translation text A Slice of Ubud in Yogyakarta (August, 2010: pp. 111-120), and Mengirim Pulang Sang Pelingsir and its translation text Sending Home the Penglingsir (August, 2008: pp. 89-98) and. The data source included the tourism texts of the GARUDA magazine, published by indomultimedia, Augustus 1st, 2010. The data collection applied a content analysis, in-depth interview, and questionnaires. The data validity employed a technique of data or source triangulation and peer debriefing. The data analysis applied an interactive model: data reduction, data display, and conclusion/verification. The results of the study showed that the translation strategies of the culture-specific words, terms, or expressions in the tourism text Sepotong Ubud di Yogyakarta are explained as follows: 1) translation by cultural substitution, 2) translation by loanwords with explanation, 3) translation loanwords without explanation, 4) translation by loanwords with definition, 5) translation by loanwords and cultural substitution, and 6) translation by loanwords and transfer. Those of the culture-specific words, terms, or expressions in the tourism text Mengirim Pulang Sang Pelingsi can be stated as follows: 1) translation by cultural substitution, 2) translation by loanwords with explanation, and 3) translation by loanword and transfer.   Keywords: specific-culture words, translation strategies, tourism text